Managing flood disasters in the city of Mukalla using GIS techniques - Bawahidi, Khaled Saleh; Hamdoun, Hanan Omar (Journal of agricultural, environmental and veterinary sciences, 2022)
This study aims to highlight the role of GIS technology in supporting decision makers in preventing flood hazards from populated areas, and mapping different areas most vulnerable to flood damage using GIS techniques. The data used in the study, such as the digital elevation model and satellite images, were downloaded from the Internet free of charge. The data was processed and used to identify wadis and streams which contribute to risk of floods in Mukalla city, capital of Hadramout province, Yemen, through spatial analysis using hydrological analysis tools such as flow accumulation, flow direction, etc. with the aim of building a spatial information base, resulting in the identification of the characteristics of wadis overlooking Mukalla, as well as identifying places at risk of flooding, including nearby communities. The study showed that some neighborhoods of Mukalla, particularly the Region of Dees al -Mukalla, are more vulnerable to flooding because there are several main wadis that flow into them and pose a significant risk to the population as a result of the severity of the drainage and its passage into communities.
Keywords: GIS; disasters; floods